Sur les normalisations d’un espace projectif engendrées par un réseau donné dans cet espace - Basilev, V. T. (Lithuanian Mathematical Journal, 1966)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. Т. Базылев. О нормализациях проективного пространства, порождаемых заданной в нем сетью V. T. Bazylevas. Projektyvinės erdvės normalizacijų, gaunamų iš duoto joje tinklo, klausimu